Pengaruh Karakteristik Individu, Disiplin Kerja dan Kepuasan Kerja Terhadap Etos Kerja - Hermayanti Hermayanti; Yustina Maro (Peneliti.net, 2022)
Work ethic is a positive and foundational behavior that includes the driving motivation, main characteristics, basic spirit, basic thoughts, code of ethics, moral code, code of conduct, attitudes, aspirations, beliefs, principles, and standards. This study aims to determine the effect of individual characteristics, work discipline and job satisfaction on the work ethic of employees, either partially or simultaneously. The sample is 28 employees. Collecting data using observation, interviews, questionnaires, and literature study. Hypothesis testing using t test and F test. The results showed that partially individual characteristics, work discipline and job satisfaction had a significant positive effect on employee work ethic. Simultaneously individual characteristics, work discipline and job satisfaction have a significant positive effect on the work ethic of employees